2003
DOI: 10.1890/01-0625
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Water Constraints on Herbivore Foraging in the Kruger National Park, South Africa

Abstract: Abstract. At a landscape scale, the combined influence of biotic and abiotic factors may determine the distribution patterns of large herbivores in African savanna ecosystems. Herbivores foraging in these ecosystems may become nutritionally stressed during an annual dry season when both forage quality and quantity are reduced. Additionally, the locations of water sources may impose a landscape-scale constraint on dry-season herbivore distributions. We used logistic regression to analyze 13 years of aerial cens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
264
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(281 citation statements)
references
References 27 publications
13
264
1
3
Order By: Relevance
“…Buffalos are grazers which are known to be relatively water dependent in order to supplement the low water content in grass with frequent drinking (Redfern et al, 2003). A study done by Smit and Grant (2009) showed that buffalo occurred 1.5km from surface water sources while other grazer species occurred approximately 2km from surface water sources.…”
Section: Location Of Water Points Visited By Different Speciesmentioning
confidence: 99%
“…Buffalos are grazers which are known to be relatively water dependent in order to supplement the low water content in grass with frequent drinking (Redfern et al, 2003). A study done by Smit and Grant (2009) showed that buffalo occurred 1.5km from surface water sources while other grazer species occurred approximately 2km from surface water sources.…”
Section: Location Of Water Points Visited By Different Speciesmentioning
confidence: 99%
“…At the landscape-scale, the often patchy distribution of resource availability over time drives distribution patterns of large herbivores (Fryxell 1991, Bailey et al 1996, Wilmshurst et al 1999, Allred et al 2011, Smit 2011). Forage quality for large herbivores can be constrained by access to reliable water sources (Bailey et al 1996, Redfern et al 2003. As such, access to water imposes a limitation on herd distributions across the landscape and regulates an animal's ability to access both high quality and quantities of forage (Redfern et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Forage quality for large herbivores can be constrained by access to reliable water sources (Bailey et al 1996, Redfern et al 2003. As such, access to water imposes a limitation on herd distributions across the landscape and regulates an animal's ability to access both high quality and quantities of forage (Redfern et al 2003). Limitations on grazing distances from water sources vary among ungulate species according to digestive throughput rate, fecal moisture content, urine volume and osmolality and other physiological and morphological characteristics associated with the grazer's ability to maintain an optimal temperature and water balance (Cain et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations